Evaluation of chitosan-anionic polymers based tablets for extended-release of highly water-soluble drugs - Yang Shao; Liang Li; Xiangqin Gu; Linlin Wang; Shirui Mao (Elsevier, 2015)
The objective of this study is to develop chitosan-anionic polymers based extended-release tablets and test the feasibility of using this system for the sustained release of highly water-soluble drugs with high drug loading. Here, the combination of sodium valproate (VPS) and valproic acid (VPA) were chosen as the model drugs. Anionic polymers studied include xanthan gum (XG), carrageenan (CG), sodium carboxymethyl cellulose (CMC-Na) and sodium alginate (SA). The tablets were prepared by wet granulation method. In vitro drug release was carried out under simulated gastrointestinal condition. Drug release mechanism was studied. Compared with single polymers, chitosan-anionic polymers based system caused a further slowdown of drug release rate. Among them, CS-xanthan gum matrix system exhibited the best extended-release behavior and could extend drug release for up to 24 h. Differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) studies demonstrated that polyelectrolyte complexes (PECs) were formed on the tablet surface, which played an important role on retarding erosion and swelling of the matrix in the later stage. In conclusion, this study demonstrated that it is possible to develop highly water-soluble drugs loaded extended-release tablets using chitosan-anionic polymers based system.